PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA KELAS V SDN 15 PEMULUTAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the Project-Based Learning (PjBL) model on students’ mathematical conceptual understanding in Grade V at SDN 15 Pemulutan. The background of this study is based on the low level of students’ understanding of mathematical concepts and the dominant use of conventional teaching methods that do not actively engage students in the learning process. The research method employed was an experimental study with a two-group design, consisting of an experimental class that applied the PjBL model and a control class that used conventional teaching methods. Data were collected through a validated test of mathematical conceptual understanding and analyzed using a t-test at a 5% significance level. The results showed that the average posttest score of students in the experimental class was 73.31, which was higher than the average posttest score of the control class at 60.52. The t-test results yielded a t-value of 2.186 with a significance value of 0.036 < 0.05. Therefore, it can be concluded that the implementation of the Project-Based Learning model has a significant effect on students’ mathematical conceptual understanding. This improvement occurred because, in PjBL-based learning, students are actively involved in planning, implementing, and completing projects related to mathematical material, particularly in data collection and data presentation. Through project activities, students learn to collaborate in groups, engage in discussions, express opinions, and relate mathematical concepts to real-world problems in their surrounding environment. This contextual and student-centered learning process encourages the development of active participation, collaboration skills, and critical thinking abilities, resulting in a more meaningful understanding of mathematical concepts that can be applied in daily life.